CRYSTAL SYMMETRY AND CHEMICAL COMPOSITION OF YUKONITE: TEM STUDY OF SPECIMENS COLLECTED FROM NALYCHEVSKIE HOT SPRINGS, KAMCHATKA, RUSSIA AND FROM VENUS MINE, YUKON TERRITORY, CANADA - Nishikawa O.; Okrugin V.; Belkova N.; Saji I.; Shiraki K.; Tazaki K. (My University, 2006)
Yukonite, a rare arsenic-bearing hydrous mineral, the crystal symmetry and variety in chemical composition of which have so far been insufficiently studied, has been found in the modern deposit of Nalychevskie hot springs in Central Kamchatka, Russia. This is the first finding of yukonite in Eastern Eurasia and Siberia. Yukonite specimens from Nalychevskie hot springs and from Venus Mine in Yukon Territory, Canada, have been investigated using an analytical transmission electron microscope (TEM). Yukonite is a crystalline substance with extremely thin (~5 nm) platy morphology. Yukonite from Venus Mine forms brittle aggregates in which grains are irregularly bent and randomly distributed. At Nalychevskie hot springs, yukonite occurs as single plates, coexisting with some amorphous material of similar composition. Intensity distributions in electron diffraction indicate that most plates of yukonite at Nalychevskie hot springs have orthorhombic symmetry, but some are hexagonal with ahex = 11.3 Å. The orthorhombic cell is C-centred with aorth = √/3ahex, borth = ahex. High-resolution images of edge-on mounts indicate that the periodicity normal to the planes is d001 = 11.2 Å. Yukonite from Nalychevskie hot springs contains anomalously high Si relative to that in yukonite from Venus Mine and that reported previously. Strong negative correlation between As and Si indicates that Si substitutes for As in the structure. © 2006 The Mineralogical Society.
Keywords: ARSENIC MINERAL; CHEMICAL COMPOSITION; CRYSTAL SYMMETRY; TEM; YUKONITE